MEMPERKUAT ORGANIZATIONAL CITIZENSHIP BEHAVIOR: PERAN KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL - Kurniawan, Ignatius Soni; Hidayanti, Faitul; Hidayanti, Faitul (Fakultas Ekonomi Universitas Kadiri, 2021)
Having employees who have extra-role performance is a benefit to the organization. The study was intended to determine the effect of job satisfaction directly on Organizational Citizenship Behavior (OCB) and indirectly through organizational commitment. This study uses primary data collected through a questionnaire survey. The sample size was 99 respondents from 132 employees of the Balai Besar Kerajinan Batik (BBKB) Yogyakarta. The study used simple, multiple regression analysis techniques, and tested the mediation model with the Sobel test. The findings have implications for organizational leaders to consider strengthening job satisfaction and organizational commitment in policies to improve OCB.